Understanding the Mediating Role of Gastronomic Experiences in a World Heritage Site: An Explanatory Approach to the Case of Córdoba (Spain) - Laura Ortega-Pérez; Cándida María Domínguez-Valerio; Consolación Pascual-García; María del Rosario Ruiz-Robles (Heritage)
Gastronomy is an essential element in the visitor’s experience in a given destination, being even more important in those destinations with an important cultural heritage. The study focused on the city of Córdoba (Spain), known for its extensive cultural heritage and for being the city with the most World Heritage declarations in the world, with four of them. Based on a total of 467 valid questionnaires, a structural equation analysis (PLS-SEM) was carried out. Of a total of four hypotheses proposed, the influence of all of them was confirmed except for the one that hypothesized an influence of perceived gastronomic value on loyalty to a gastronomic destination, thus confirming the overall mediating effect of gastronomic experiences between the two variables mentioned above. Furthermore, the influence of gastronomic satisfaction on loyalty to a gastronomic destination was evident, with no mediating effect of gastronomic experiences in this case. The results obtained can be of great help to decision-makers, both public and private, in establishing gastronomic proposals that are genuine, sensorially rich, and strongly culturally rooted, thus enhancing the cultural experience.